Comparison of Mixed Marshall Characteristics Asphalt Concrete AC-BC Post-Immersion Lime Filler in River Water And Seawater - Hasanuddin; Mohamad Ikbal Z. Abd. Wahid; Dewi Ayu Setiawati (Universitas Muhammadiyah Palu, 2025)
Indonesia has several roads adjacent to the coast so that if the sea tide rises, the road will be flooded by floodwater. One of them is Palu City which often experiences rob events. To achieve quality road conditions, it is necessary to provide handling technology with economic value, one of the alternatives is to provide fillers that can be used in asphalt concrete mixtures, namely lime. The purpose of the study was to evaluate and compare the characteristics of marshall mixed asphalt concrete AC-BC lime filler post-immersion in river water and seawater. The type of research used is experimental research by making samples or test objects carried out at the Transportation and Highway Laboratory, Faculty of Engineering, Tadulako University. The researcher took samples directly at the research location and used as raw materials for testing and obtained data from the results of the test through the laboratory. The results of the Marshall test of AC-BC asphalt concrete mixture lime filler on 2 types of immersion, The immersion of AC-BC asphalt concrete mixture using river water and seawater showed a decrease in stability value. In immersion in river water, the lowest was 3.94% and the highest stability decrease percentage value was 22.63%. The lowest percentage value of stability decline in immersion in seawater was 3.69% and the highest stability reduction percentage value was 29.23%. Soaking the AC-BC asphalt concrete mixture using river water and seawater showed an increase in flow value. The value of the percentage of increase in flow in immersion in river water was the lowest of 0.07% and the value of the highest percentage of flow increase was 1.30%. The lowest flow increase percentage value in seawater immersion was 0.14% and the highest flow increase percentage value was 1.47%. Then for the soaking of AC-BC asphalt concrete mixture using river water and seawater, it showed a decrease in the Marshall Quotient (MQ) value. The percentage value of MQ reduction in immersion in river water is the lowest of 6.70% and the highest MQ reduction percentage value is 46.05%. The value of the MQ decrease in immersion in seawater was the lowest at 8.37% and the highest MQ reduction percentage value was 52.73%.